Pengembangan E-Modul dengan Model Problem Based Learning pada Mata Pelajaran PAI - Nur Aisyah; Santi Laili Safitri; Fatimatus Zahra; Dwi Irma Santoso (MANAZHIM, 2021)
Learning during the current pandemic requires innovation so that students do not miss the material. One thing that teachers can do is develop e-modules. The purpose of the e-module is so that students can continue to study independently according to their respective speeds and abilities. Research method using the Borg and Gall model with 8 systematic steps. The results of the study show that the e-module can be used properly according to expert validation and students input.